Equal channel angular extrusion of aluminium – multi wall carbon-nanotubes composites - Mohamed Adil Akbar Abdullah Morgan. (2010)
Research in MMCs, are highly rated due to the projected use of these composites in the applications such as aerospace and electrical research field. However CNT- based MMCs have been on the receiving end of lesser attention. This FYP incorporates the use of Aluminium as the matrix for the MMC with CNTs as the reinforcing phase, and have prospects due to their electrical and thermal characteristics. In this particular FYP, the variation of the properties are researched for the purpose of establishing and characterising the materials according to their bulk material properties, which may then create a platform for higher end research or direct application in a field of engineering. The specimens of the research comprise of a pure aluminium sample, a 0.5 weight % CNT specimen, a 1.0 weight % CNT specimen and a 2.0 weight % CNT specimen, which have been manufactured through the means of ball-milling, spark-plasma sintering and lastly equivalent channel angular extrusion. However, due to the failure of the brittle specimens in the physical ECAE process, another approach was taken. Finite Element Modelling was carried out with different angles of 12°, 20° and 28° respectively to observe the plastic strains and Von Mises stress variations in the specimens. From the results, it illustrates that for an outer angle of 12° or there within, homogeneity of strain and stresses in the specimens can be obtained.